Travel Behaviour Analysis of Local Residents during Evacuation in the Event of Tsunami in Bali Province - D.M Priyantha Wedagama (Institut Teknologi Bandung, 2012)
Abstract. This study investigates local residents travel behaviour in Bali Province during evacuation in the event of a tsunami. The analyses include shelter and human response time choices. Data were collected by distributing Stated Preferences (SP) questionnaires to local residents from two coastal areas of Kuta and Sanur. Data include household preferences to shelter and response time choices, personal data, socio-economy, a distance of residence to the coastline, and the experience of natural disasters. The analyses are conducted using binary logistic regression model. The study shows that significant factors influencing shelter choices are education levels, car ownership and no natural disaster knowledge. Significant factors influencing response time choices are age, a household with total income per month less than 3 million rupiahs, and car and motorcycle ownerships. The study suggests that the local government should begin to disseminate the alternative types and locations of shelter during an evacuation, considering the limited ability of the government in providing shelter in case of a tsunami. In addition, the local government is expected to consider the types and number of mass transport fleet that must be provided when the tsunami hit.Abstrak. Studi ini meneliti prilaku evakuasi penduduk lokal jika terjadi tsunami di Provinsi Bali yang meliputi pilihan tujuan perjalanan ke tempat berlindung (privat atau publik) dan waktu respon (cepat atau lambat). Data dikumpulkan dari dua wilayah pantai yaitu pantai Kuta dan Sanur dengan menyebarkan kuisioner Stated Preferences (SP) kepada penduduk lokal. Data meliputi preferensi rumah tangga terhadap pemilihan tempat berlindung dan pilihan waktu respon jika terjadi tsunami, data pribadi, sosial ekonomi, jarak tempat tinggal ke tepi pantai, dan pengalaman terhadap bencana alam Analisis dilakukan menggunakan model regresi logistik biner. Hasil studi menunjukkan faktor-faktor yang berpengaruh terhadap pemilihan tempat berlindung adalah tingkat pendidikan, jumlah unit mobil yang dimiliki rumah tangga dan tidak mempunyai pengalaman terhadap bencana alam lainnya (selain Tsunami). Faktor-faktor yang berpengaruh terhadap waktu respon penduduk adalah umur, total pendapatan rumah tangga per bulan kurang dari 3 juta rupiah, jumlah unit mobil dan sepeda motor yang dimiliki rumah tangga. Studi ini menyarankan agar pemerintah daerah mulai mensosialisasikan alternatif tipe dan lokasi tempat berlindung saat evakuasi, mengingat kemampuan pemerintah yang tentunya terbatas di dalam menyediakan tempat berlindung jika terjadi tsunami. Pemerintah daerah juga diharapkanmengkaji tipe dan jumlah armada angkutan masal yang harus disediakan saat terjadi tsunami.